Pour une théorie littéraire illustrée - Wandzioch, Magdalena (Romanica Silesiana)
The artists and the theorists have always been fascinated by and driven to discover the relationship between arts, like painting and literature. What may come out as a surpise for those who love books, as for those who admire painting, is the illustrated theory of literature by Roger Caillois, whose background is not in literature or in painting, but in sociology. His work entitled Au coeur du fantastique published by Gallimard in 1965 and illustrated with famous paintings as well as less known ones has brought together literary criticism and painting by focusing on the theory of the genre of fantastique in literature and in painting, pointing at the similarities rather than differences. However from the 18th century, literature has beeen considered to have straight connection with time, what means being subject to chronosyntaxe (time syntax) while painting has been linked to space what signifies being subject to toposyntaxe (space syntax). The Caillois’s theory allows the public to guess what lies in the profoundity of fantastique, intangible but identified in art. Key words: Fantastique, literature, painting, Roger Caillois.